Teacher's Effort in Improving the Quality of Islamic Religion Education - Sri Hafriani (International Journal on Education Issues, 2025)
Purpose - This makes researchers interested in conducting research at the school. Researchers want to know what efforts teachers make in improving the quality of Islamic religious education in schools, and what are the causal factors that influence teachers' efforts in improving the quality of Islamic religious education. Design/Methodology/Approach - Researchers conducted research using a qualitative descriptive method. In this study, researchers took several samples, both from teachers, principals, vice principals, and heads of staffs. Findings -From the results of the study, there are four efforts of teachers in improving the quality of Islamic religious education, namely efforts to improve Islamic religion related to student learning, teacher efforts related to the profession, teacher efforts related to teacher cooperation with parents, and teacher efforts related to student morals, and teacher efforts in holding boarding school programs.  Factors known in the study, namely there are several factors. First, teacher readiness factors, student readiness factors, family factors, and environmental factors. And also, from the study the researcher found differences between the two classes at SMP Negeri 7, namely the regular class and the boarding school class. Originality/Value - The differences between students from the two different classes can be seen from their polite morals. Children who attend boarding school classes know more about how to be polite, compared to children from regular classes. This is because students who attend classes until the afternoon get more learning both in the field of religion and other fields. And also, boarding school students live at SMP Negeri 7 Simeulue Timur.